Intimate partner violence prevalence and HIV risks among women receiving care in emergency departments: implications for IPV and HIV screening. Issue 4 (23rd March 2007) - El-Bassel, Nabila; Gilbert, Louisa; Wu, Elwin; Chang, Mingway; Gomes, Carla; Vinocur, Danielle; Spevack, Theodore
Abstract : Objective: To examine (1) the prevalence of experiencing physical, injurious and sexual intimate partner violence (IPV) and (2) the associations between HIV risks and different types of IPV among women receiving care in an inner city emergency department (ED). Methods: A cross-sectional survey that elicited self-reported HIV risks and IPV among a random sample of 799 women receiving ED care. Multiple logistic regression was used to examine the associations between HIV risk and IPV, with covariance adjustment for potentially confounding sociodemographics. Results: 49.6% of the women reported a history of any form (ie, minor and severe type) of physical, injurious and/or sexual IPV, 15% severe sexual coercion (rape) over life time and 11.8% IPV in the past 6 months. Women who reported engaging in sex with a HIV-infected partner or an injecting drug user (IDU), having multiple partners in the past 12 months and injecting drugs were significantly more likely to have experienced any form of physical/injurious IPV, severe physical/injurious IPV and any form of sexual IPV in the past 6 months. In addition, women with multiple partners in the past 12 months and women who reported injecting drugs were significantly more likely to indicate having experienced a severe form of sexual IPV in the past 6 months. Conclusion: For many women receiving care in EDs, IPV and several HIV risk behaviours are frequent, co-occurring health problems. HIV testing and routine IPV inquiry in ED settings offer an important opportunity to identify women who are affected by these overlapping epidemics and refer them to appropriate treatment services.